Rich and Healthy Strategies as an Impact of Waqf Law (Integration of Islamic Humanizing Values) - Senki Nurachmadi; Moh. Sholeh Afyuddin; Agus Mubarok (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Abstract: This study aims to explore the Impact Integration of Islamic Humanizing Values about Waqf has extraordinary benefits, not only for the wakif (the person who makes the waqf) but also has an extraordinary impact on the community, especially waqf used in productive activities whose results are distributed according to the purpose of the waqf. Activities and production results are more oriented towards the economic and da'wah sectors, where the products are material/external, commonly called productive waqf. This causes the understanding of productive waqf to be no better than monetary waqf, even though productive waqf has a positive impact on the physical and even spiritual. This study forms the assumption that waqf is useful as a law of Allah's command to carry out waqf. The essence of the impact of the law of waqf consists of four points of support: a strong body, a healthy brain, a healthy soul, and rich (sufficient). Happy people are proven to have: pleasure in everyday life, feelings of the heart, satisfaction in marriage, work, and the miracle of health recovery. The result of the exploration is reasonable that the waqif whose waqf is utilized profitably as one of the impacts of waqf law is proven to feel an extraordinary impact in their lives.